2017
DOI: 10.1007/s00330-017-4786-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary and metastatic ovarian cancer: Characterization by 3.0T diffusion-weighted MRI

Abstract: ObjectivesWe aimed to investigate whether apparent diffusion coefficients (ADCs) measured by 3.0T diffusion-weighted magnetic resonance imaging (DWI) associate with histological aggressiveness of ovarian cancer (OC) or predict the clinical outcome. This prospective study enrolled 40 patients with primary OC, treated 2011-2014.MethodsDWI was performed prior to surgery. Two observers used whole lesion single plane region of interest (WLsp-ROI) and five small ROIs (S-ROI) to analyze ADCs. Samples from tumours and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 33 publications
4
16
1
Order By: Relevance
“…Recent studies and meta‐analyses have shown a strong correlation between ADC and cellularity and a good association between ADC and cell proliferation (in terms of KI67 nuclear protein) in ovarian cancer, mainly of the serous subtype . In agreement with studies on other tumor types, our results show that response to treatment is clearly identified using mono‐exponential fitting with b values higher than 100 s/mm 2 .…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies and meta‐analyses have shown a strong correlation between ADC and cellularity and a good association between ADC and cell proliferation (in terms of KI67 nuclear protein) in ovarian cancer, mainly of the serous subtype . In agreement with studies on other tumor types, our results show that response to treatment is clearly identified using mono‐exponential fitting with b values higher than 100 s/mm 2 .…”
Section: Discussionsupporting
confidence: 89%
“…Tissue samples were embedded in paraffin and cut into 5-μm-thick sections. Next, the sections were processed for staining with hematoxylin-eosin, VEGF-A (1:250; Santa Cruz), VEGF-C (1:20; Novus), VEGF-D (1:20; Santa Cruz), VEGFR1 (1:15; Santa Cruz), VEGFR2 (1:750; Cell Signaling), and VEGFR3 (11:000, Millipore/Chemicon) [2125].…”
Section: Methodsmentioning
confidence: 99%
“…A possible explanation may be that cancer nests with extremely low ADC values have the potential for rapid and aggressive cancer growth. Consistent with this idea, a close relationship was found between low ADC values and expression levels of Ki-67 protein, which is considered a molecular marker of accelerated cell proliferation [ 20 , 21 ]. Furthermore, a high level of Ki-67 protein expression was reportedly associated with high mortality of patients with various subtypes of salivary gland carcinomas [ 16 , 22 ].…”
Section: Discussionmentioning
confidence: 75%